PENGARUH LATIHAN DOUBLE LEG BOUND TERHADAP POWER OTOT TUNGKAI TIM BOLA VOLI PUTERA SMA NEGERI 1 DAYUN KABUPATEN SIAK - Febri Alfian Andrias; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine "The effect of Double Leg Bound exercise has an effect on the results of Leg Muscle Power for the Boys Volleyball Team of SMA Negeri 1 Dayun, Siak Regency. This research was conducted at the volleyball court of SMA Negeri 1 Dayun, Jl. KH. Ahmad Dahlan, Sialang Sakti Village, Siak Regency. This study uses one group, so this study uses a one-group pretest-posttest design approach. In this design there is a pretest before being given treatment. From the analysis it can be concluded that there is an effect of Double Leg Bound exercise on increasing leg muscle power. Programmed and continuous training, the more routinely we do the Double Leg Bound exercise, the better the team's leg muscle power will be. It is clear that to get the results of leg power, it can be increased by doing the Double Leg Bound exercise. This can be seen from the results obtained by using the Double Leg Bound exercise, the results of the leg power obtained are also increased, especially in the Riau Province Satpol Putra team, which this research has held.Key Words: Double Leg Bound Exercise, Leg Muscle Power